Preparation method of desulfurization and decarburization agent
Highly efficient desulfurization and Desulfurization and decarbonizer with decarbonization ability solves the problems of low efficiency and secondary pollution in traditional technologies.
Patent Information
- Application Number
- CN202510020780.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional desulfurization technology has problems such as low separation efficiency and secondary pollution of solid waste, and the residual low concentration of sulfur dioxide will reduce the subsequent purification efficiency of carbon dioxide.
Using 3,3-dimethylquinoline-2,4(1H,3H)-dione and tributylene as monomers to polymerize under acidic conditions through hydroxyalkylation reaction to obtain an amorphous polynanoporous polymer, and then Ionization is carried out by Hoffman alkylation reaction with iodoethane and amino groups, and finally a desulfurization and decarburizing agent is obtained by anion exchange with sodium hydroxide.
The obtained desulfurization and decarbonizer has excellent sulfur dioxide selectivity, high sulfur dioxide dehydration rate, good carbon dioxide coabsorbance rate and regeneration performance, and solves the problems of low efficiency and secondary pollution in traditional technology.
Smart Images

Figure CN119431751A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of desulfurization and decarbonization agents, and more specifically, to a method for preparing a desulfurization and decarbonization agent. Background Art
[0002] Although the supply of clean energy has been increasing with the advancement of science and technology in recent years, fossil fuels such as oil and coal still dominate. In addition to a large amount of nitrogen, the tail gas produced by the combustion of fossil fuels in thermal power plants and large-scale industrial production also contains nitrogen monoxide, sulfur dioxide, oxygen, carbon dioxide, etc. The sulfur dioxide in the tail gas can cause equipment corrosion or form acid rain, which has an adverse effect on the environment and human health, while carbon dioxide can indirectly cause natural disasters such as global warming and glacier melting. Therefore, removing sulfur dioxide and carbon dioxide from tail gas is extremely important for achieving environmental pollution prevention and control and responding to climate change.
[0003] Although traditional desulfurization technologies such as limestone / gypsum can remove more than 90% of sulfur dioxide, they have problems such as low separation efficiency and secondary pollution of solid waste. In addition, the residual low-concentration sulfur dioxide will significantly reduce the subsequent purification efficiency of carbon dioxide. Therefore, the development of new energy-saving materials that can efficiently desulfurize and decarbonize and are renewable is a major challenge in the development of tail gas desulfurization and decarbonization technology. Summary of the invention
[0004] In order to further improve the desulfurization and decarbonization efficiency in fossil fuel tail gas, the present application provides a method for preparing a desulfurization and decarbonization agent.
[0005] In the first aspect, the present application provides a desulfurization and decarbonization agent, which adopts the following technical solution: A desulfurization and decarbonization agent, the structure is as follows: .
[0006] By adopting the above technical scheme, the desulfurization and decarbonization agent has a large number of microporous networks and a large number of electron-rich oxygen atoms and nitrogen atoms, which is beneficial to enhancing the capture and adsorption capacity of sulfur dioxide and carbon dioxide, and further improves the adsorption capacity of sulfur dioxide and carbon dioxide by introducing hydroxyl ions into the polymer skeleton structure.
[0007] In a second aspect, the present application provides a method for preparing a desulfurization and decarbonization agent.
[0008] The preparation method of the desulfurization and decarbonization agent comprises the following steps: S1, 3,3-dimethylquinoline-2,4(1H,3H)-dione, triptycene and trichloroethane are mixed and stirred for 20-30 minutes, and then pre-cooled trifluoroacetic acid is added dropwise under a nitrogen atmosphere while maintaining the temperature below 0°C, and then stirred at room temperature for reaction for 4-6 days, and then ethanol aqueous solution is added to the reaction solution, and then suction filtration is performed, and then the filter cake is washed with deionized water, acetone, trichloroethane and ethanol at least twice in sequence, and vacuum dried at 100-120°C for 10-12h to obtain polymer 1; S2, dispersing polymer 1 in dimethyl sulfoxide, keeping the environment dark, then adding iodoethane, stirring at room temperature for 20-24 hours, then adding ethanol, filtering, washing the filter cake with water and ethanol respectively, and vacuum drying at 100-120° C. for 10-12 hours to obtain polymer 2; S3, ion exchange polymer 2 with potassium hydroxide solution at 70-80°C for more than 5 times, each time for 1.5-2h, then wash with deionized water, and vacuum dry at 100-120°C for 10-12h to obtain a desulfurization and decarbonization agent.
[0009] By adopting the above technical scheme, 3,3-dimethylquinoline-2,4(1H,3H)-dione and triptycene are used as monomers to obtain an amorphous multi-nanoporous polymer 1 through hydroxyalkylation reaction under acidic conditions, and then ionized through Hofmann alkylation reaction of iodine and amino group, and finally a desulfurization and decarbonization agent is obtained through anion exchange with sodium hydroxide. The obtained desulfurization and decarbonization agent has excellent sulfur dioxide selectivity, high sulfur dioxide removal rate, and also has relatively good carbon dioxide co-absorption rate and regeneration performance.
[0010] Preferably, the usage ratio of 3,3-dimethylquinoline-2,4(1H,3H)-dione, triptycene, trichloroethane and trifluoroacetic acid in S1 is (4-5.5) mol: (6-8) mol: (200-280) mL: (10-12) mol.
[0011] By adopting the above technical solution, the network pore size of the desulfurization and decarbonization agent prepared at this ratio is smaller, and the capture and adsorption capacity of sulfur dioxide and carbon dioxide is optimal.
[0012] Preferably, the volume ratio of ethanol to water in the ethanol aqueous solution in S1 is (1-1.5): (3-5).
[0013] By adopting the above technical solution, the ethanol aqueous solution at this concentration is conducive to the precipitation of polymer 1.
[0014] Preferably, the usage ratio of polymer 1, dimethyl sulfoxide and ethyl iodide in S2 is (1-2) g: (20-30) mL: (1.2-2.8) mL.
[0015] By adopting the above technical solution, this ratio of ethyl iodide can make the polymer ionized more completely.
[0016] Preferably, the usage ratio of polymer 2 to potassium hydroxide solution in S3 is (1.2-1.5) g: (25-32) mL.
[0017] Preferably, the concentration of the potassium hydroxide solution is 1-1.2 mol / L.
[0018] By adopting the above technical solution, the degree of polymer ion exchange is maximized.
[0019] In a second aspect, the present application provides an application of a desulfurization and decarbonization agent for desulfurization and decarbonization in fossil fuel tail gas.
[0020] In summary, this application has the following beneficial effects: 1. The present application adopts 3,3-dimethylquinoline-2,4(1H,3H)-dione and triptycene as monomers to obtain an amorphous multi-nanoporous polymer 1 through hydroxyalkylation reaction under acidic conditions, and then ionizes it through Hofmann alkylation reaction of iodine and amino group, and finally obtains a desulfurization and decarbonization agent through anion exchange with sodium hydroxide. The obtained desulfurization and decarbonization agent has excellent sulfur dioxide selectivity, high sulfur dioxide removal rate, and also has the advantages of relatively good carbon dioxide co-absorption rate and regeneration performance.
[0021] 2. The desulfurization and decarbonization agent prepared in the present application has a large number of microporous networks and a large number of electron-rich oxygen atoms and nitrogen atoms, which are beneficial to enhancing the capture and adsorption capacity of sulfur dioxide and carbon dioxide, and further improves the adsorption capacity of sulfur dioxide and carbon dioxide by introducing hydroxyl ions into the polymer skeleton structure.
[0022] 3. The preparation method of the present application is simple, the raw materials are readily available, and the production can be easily expanded; the prepared desulfurization and decarbonization agent can be recycled and regenerated, and has the characteristics of energy saving. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : Flow chart for preparation of desulfurization and decarbonization agent of this application.
[0024] Figure 2 : Infrared spectrum of the desulfurization and decarbonization agent of this application.
[0025] Figure 3 : SEM image of the desulfurization and decarbonization agent of this application.
[0026] Figure 4 : Nitrogen adsorption and desorption isotherms of the desulfurization and decarbonization agent of the present application, in which the solid points are adsorption points and the hollow points are desorption points. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0029] Example 1 A desulfurization and decarbonization agent, the structure is as follows: .
[0030] The desulfurization and decarbonization agent is prepared by the following method (such as Figure 1 shown): S1, 4 mol of 3,3-dimethylquinoline-2,4(1H,3H)-dione, 6 mol of triptycene and 200 mL of trichloroethane were mixed and stirred for 20 min, and then 10 mol of pre-cooled trifluoroacetic acid was added dropwise under a nitrogen atmosphere while keeping the temperature below 0°C, and then stirred at room temperature for 4 days, and then an ethanol aqueous solution (the volume ratio of ethanol to water in the ethanol aqueous solution was 1:3) was added to the reaction solution, and then suction filtered, and then the filter cake was washed twice with deionized water, acetone, trichloroethane and ethanol in sequence, and vacuum dried at 100°C for 12 h to obtain polymer 1 (yield 92.4%); S2, 1 g of polymer 1 was dispersed in 20 mL of dimethyl sulfoxide, kept in a dark environment, and then 1.2 mL of ethyl iodide was added, followed by stirring at room temperature for 20 h, and then ethanol was added, filtered, and the filter cake was washed with water and ethanol respectively, and vacuum dried at 100 ° C for 12 h to obtain polymer 2 (yield 95.7%); S3, 1.2 g of polymer 2 was subjected to ion exchange with 25 mL of 1 mol / L potassium hydroxide solution at 70 °C for 5 times, each time for 1.5 h, and then washed with deionized water and vacuum dried at 120 °C for 12 h to obtain a desulfurization and decarbonization agent (yield 98.5%).
[0031] Example 2 A desulfurization and decarbonization agent is prepared by the following method: S1, 5 mol of 3,3-dimethylquinoline-2,4(1H,3H)-dione, 7 mol of triptycene and 240 mL of trichloroethane were mixed and stirred for 25 min, and then 11 mol of pre-cooled trifluoroacetic acid was added dropwise under a nitrogen atmosphere while keeping the temperature below 0°C, and then stirred at room temperature for 5 days, and then an ethanol aqueous solution (the volume ratio of ethanol to water in the ethanol aqueous solution was 1.2:4) was added to the reaction solution, and then suction filtered, and then the filter cake was washed 3 times with deionized water, acetone, trichloroethane and ethanol in sequence, and vacuum dried at 110°C for 11 hours to obtain polymer 1 (yield 91.2%); S2, 1.5 g of polymer 1 was dispersed in 25 mL of dimethyl sulfoxide, kept in a dark environment, and then 2 mL of iodoethane was added, followed by stirring at room temperature for 22 h, and then ethanol was added, filtered, and the filter cake was washed with water and ethanol respectively, and vacuum dried at 110 ° C for 11 h to obtain polymer 2 (yield 96.1%); S3, 2 g of 1.3 polymer was subjected to ion exchange with 28 mL of 1.1 mol / L potassium hydroxide solution at 75°C for 6 times, each time for 1.5 h, and then washed with deionized water and vacuum dried at 110°C for 11 h to obtain a desulfurization and decarbonization agent (yield 99.3%).
[0032] Example 3 A desulfurization and decarbonization agent is prepared by the following method: S1, 5.5 mol of 3,3-dimethylquinoline-2,4(1H,3H)-dione, 8 mol of triptycene and 280 mL of trichloroethane were mixed and stirred for 30 min, and then 12 mol of pre-cooled trifluoroacetic acid was added dropwise under a nitrogen atmosphere while keeping the temperature below 0°C, and then stirred at room temperature for 6 days, and then an ethanol aqueous solution (the volume ratio of ethanol to water in the ethanol aqueous solution was 1.5:5) was added to the reaction solution, and then suction filtered, and then the filter cake was washed 4 times with deionized water, acetone, trichloroethane and ethanol in sequence, and vacuum dried at 120°C for 10 h to obtain polymer 1 (yield 93.1%); S2, (1-2) g of polymer 1 was dispersed in 30 mL of dimethyl sulfoxide, kept in a dark environment, and then 2.8 mL of ethyl iodide was added, followed by stirring at room temperature for 24 h, and then ethanol was added, filtered, and the filter cake was washed with water and ethanol respectively, and vacuum dried at 120 ° C for 10 h to obtain polymer 2 (yield 94.6%); S3, 1.5 g of polymer 2 was subjected to ion exchange with 32 mL of 1.2 mol / L potassium hydroxide solution at 80°C for 7 times, each time for 2 h, and then washed with deionized water and vacuum dried at 120°C for 10 h to obtain a desulfurization and decarbonization agent (yield 98.2%).
[0033] Performance testing (1) The desulfurization and decarbonization agent prepared in Example 1 was tested by Fourier transform infrared using ATR-FTIR spectrometer. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the desulfurization and decarbonization agent shows 680-900cm -1 In the aromatic carbon-hydrogen out-of-plane bending vibration region, 1000-1300cm -1 In the aromatic carbon-hydrogen plane bending vibration region, 1400-1500cm -1 Aromatic skeleton vibration area, 1586-1600cm -1The triptycene skeleton structure and 2960cm -1 The methyl vibration contraction peak at 1705 cm -1 The carbonyl double bond stretching vibration peak at 1315 cm -1 The characteristic peaks of dimethylquinoline-2,4(1H,3H)-dione and other carbon-nitrogen vibration peaks indicate that the desulfurization and decarbonization agent was successfully prepared.
[0034] (2) The desulfurization and decarbonization agent prepared in Example 1 was observed using an electron scanning microscope. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the desulfurization and decarbonization agents prepared in Example 1 are all formed by disorderly stacking of irregular tiny nanoparticles and present a loose network structure, which also means that they have a large specific surface area and micropore volume.
[0035] (3) The desulfurization and decarbonization agent prepared in Example 1 was tested using a specific surface area and porosity analyzer to obtain a 77K nitrogen adsorption and desorption isotherm, as shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the nitrogen adsorption isotherm of the desulfurization and decarbonization agent increases sharply when the pressure is low (P / P0<0.05), and increases slowly in the medium pressure area, which conforms to the I type adsorption isotherm morphology, indicating that the desulfurization and decarbonization agent is mainly a microporous structure. The main surface area of the desulfurization and decarbonization agent calculated by using the isotherm data is 925m 2 / g, the HK method was used to calculate that the pore size of the desulfurization and decarbonization agent is mainly concentrated around 0.8nm.
[0036] (4) Evaluation of desulfurization and decarbonization performance The desulfurization and decarbonization performance of Examples 1 to 3 and commercially available desulfurization and decarbonization agents (purchased from SMARTCORR Cisco Corrosion Systems Co., Ltd.) was evaluated by static adsorption method. The specific operation was as follows: the raw gas (containing 90% nitrogen, 0.5% sulfur dioxide, and 9.5% carbon dioxide by volume) was fully mixed and analyzed by gas chromatography; the raw gas (humidity of 75%) was then introduced into an absorption device containing 100g of desulfurization and decarbonization agent, and the raw gas was allowed to fully react in the absorption device for 20 minutes at 25°C. The tail gas after absorption was dried and then entered into the gas chromatography for composition analysis, and finally the tail gas was treated; the amount of sulfur dioxide in the desulfurization and decarbonization agent was calculated according to the iodine method, and the amount of carbon dioxide in the desulfurization and decarbonization agent was calculated by the difference method, and finally the selectivity of sulfur dioxide, the removal rate of sulfur dioxide and the co-absorption rate of carbon dioxide were obtained. The results are shown in Table 1: Table 1 Desulfurization and decarbonization performance test results
[0037] It can be seen from Table 1 that the desulfurization and decarbonization agents prepared in Examples 1 to 3 of the present application have excellent sulfur dioxide selectivity, a high sulfur dioxide removal rate, and a relatively good carbon dioxide co-absorption rate.
[0038] (5) Evaluation of regeneration performance The desulfurization and decarbonization agents after adsorption in Example 1 to Example 3 were heated at 120°C in vacuum for 40 minutes, and the desorbed gas was dried and then entered the tail gas absorption device; the amount of sulfur dioxide in the desulfurization and decarbonization agent after desorption was calculated according to the iodine method, and then the amount of carbon dioxide in the desulfurization and decarbonization agent after desorption was calculated using the difference method, and finally the desorption rate was obtained. The test results are shown in Table 2.
[0039] Table 2 Desulfurization and decarbonization performance test results
[0040] It can be seen from Table 2 that the desulfurization and decarbonization agents prepared in Examples 1 to 3 of the present application are easy to desorb, have good regenerative properties, and are energy-saving desulfurization and decarbonization agents.
[0041] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.
Claims
1. A desulfurization and decarbonization agent, characterized in that: The structure is as follows: 。 2. The method for preparing a desulfurization and decarbonization agent according to claim 1, characterized in that: The method comprises the following steps: S1, mixing 3,3-dimethylquinoline-2,4(1H,3H)-dione, triptycene and trichloroethane and stirring for 20-30 minutes, then dripping pre-cooled trifluoroacetic acid under a nitrogen atmosphere while keeping the temperature below 0°C, and then stirring and reacting at room temperature for 4-6 days, then adding ethanol aqueous solution to the reaction solution, and then filtering, and then washing the filter cake with deionized water, acetone, trichloroethane and ethanol at least twice in sequence, and vacuum drying at 100-120°C for 10-12 hours to obtain polymer 1. ; S2, disperse polymer 1 in dimethyl sulfoxide, keep it in a dark environment, then add iodoethane, stir it at room temperature for 20-24 hours, then add ethanol, filter it, wash the filter cake with water and ethanol respectively, and vacuum dry it at 100-120℃ for 10-12h to obtain polymer 2; S3, carry out ion exchange of polymer 2 with potassium hydroxide solution at 70-80℃ for more than 5 times, each time for 1.5-2h, then wash it with deionized water, and vacuum dry it at 100-120℃ for 10-12h to obtain a desulfurization and decarbonization agent.
3. The method for preparing a desulfurization and decarbonization agent according to claim 2, characterized in that: The usage ratio of 3,3-dimethylquinoline-2,4(1H,3H)-dione, triptycene, trichloroethane and trifluoroacetic acid in S1 is (4-5.5) mol: (6-8) mol: (200-280) mL: (10-12) mol.
4. The method for preparing a desulfurization and decarbonization agent according to claim 3, characterized in that: The volume ratio of ethanol to water in the ethanol aqueous solution in S1 is (1-1.5): (3-5).
5. The method for preparing a desulfurization and decarbonization agent according to claim 4, characterized in that: The usage ratio of polymer 1, dimethyl sulfoxide and ethyl iodide in S2 is (1-2) g: (20-30) mL: (1.2-2.8) mL.
6. The method for preparing a desulfurization and decarbonization agent according to claim 5, characterized in that: The usage ratio of polymer 2 to potassium hydroxide solution in S3 is (1.2-1.5) g: (25-32) mL.
7. The method for preparing a desulfurization and decarbonization agent according to claim 6, characterized in that: The concentration of the potassium hydroxide solution is 1-1.2 mol / L.
8. The use of a desulfurization and decarbonization agent as claimed in claim 1, characterized in that: Used for desulfurization and decarbonization of fossil fuel tail gas.
Citation Information
Patent Citations
Serial compounds with triptycene as framework and in bridge connection with metalloporphyrin through pyrene tetrone and preparation method therefor
CN105254639A
Flexible hydrophilic polymer capable of adsorbing-desorbing anions and cations, and preparation method and application of flexible hydrophilic polymer
CN111995714A
Adamantyl microporous material and preparation method thereof
CN114805756A
Catalytic porous polymer for selective capture and reduction of carbon dioxide
US20230234042A1
Cited By
Novel sterically hindered amine composite desulfurizer and preparation method thereof
CN121422701A
A sterically hindered amine composite desulfurizer and its preparation method
CN121422701B